MENGANALISIS POTENSI SUMBER DAYA ALAM DI DESA KELAISI TENGAH, KECEMATAN ALOR SELATAN - Mariam Atamai; Neziah Hinagay; Henderina Womakal; Petrus Mau Tellu Dony (JOURNAL OF COMMUNITY DEDICATION, 2026)
This research aims to analyze the growth potential of natural resources found in Kelaisi Tengah Village, South Alor District, Alor Regency. The research method uses a qualitative descriptive approach through field observation, interviews with the village head and local community, as well as documentation. The results of this study indicate that Kelaisi Tengah Village has several leading commodities, such as candlenut, vanilla, porang tuber, and areca nut, which have the potential to be developed as sources of community income. In addition, fertile land conditions and a supportive climate are supporting factors for the development of the plantation sector. This study concludes that the utilization of the natural resource growth potential in Kelaisi Tengah Village has a great opportunity to improve community welfare if managed sustainably and supported by relevant development programs.